New Purine Nucleoside Analogs for Acute Lymphoblastic Leukemia - Robak, Tadeusz (Clinical Cancer Drugs, 2014)
Acute lymphoblastic leukemia is the most common malignant disease in childhood, and accounts for approximately 20% of acute leukemias in adults. Two thirds of the cases are diagnosed in children and adolescents, making ALL the most common cancer within this specific population. Recently, three novel purine nucleoside analogs (PNAs): clofarabine (CAFdA), nelarabine (ara-G) and forodesine (BCX-1777, immucillin H) have been synthesized and introduced into clinical trials for this leukemia. CAFdA is the most promising PNA in current clinical trials in pediatric and adult patients with acute leukemias. Nelarabine has consistently been reported to be more cytotoxic in T-lineage than in B-lineage leukemias. CAFdA and nelarabine have been approved for the treatment of refractory patients with acute lymphoblastic leukemia and lymphoblastic lymphoma. Unlike other PNA, forodesine is not incorporated into DNA but displays a highly selective purine nucleoside phosphorylase inhibitory action. Forodesine has been investigated for the treatment of T-cell malignancies, including T-ALL. This article summarizes recent achievements in the mechanism of action, pharmacological properties and clinical activity and toxicity as well as the emerging role of novel PNAs in acute lymphoblastic leukemia.
Keywords: clofarabine